RELASI GENDER DALAM KELUARGA PEREMPUAN OJEK-ONLINE DI SURAKARTA (Studi Deskriptif Pada Keluarga Perempuan Ojek-Online Go-Jek di Surakarta) - Devi Yulianita Victorine; Thomas Aquinas Gutama (Universitas Sebelas Maret (UNS), 2019)
This research aims to determine the activities division, access-control distribution, and the factors that influence the division of activities and access-control in the families of women-online taxibikers “Go-Jek” in Surakarta. Talcott Parsons’ Structural Functionalism theory is used in this research. This is a qualitative descriptive research. The data were collected from indepth interview, observation, and documentation. The subjects were the families of women-online taxibikers “Gojek in Surakarta. The researcher used source triangulation to examine the validity of the data. In analyzing the data, the researcher used Miles and Huberman’s theory which consisted of data reduction, data presentation, and drawing conclusion. In addition, Harvard’s analysis technique was also used to observe the gender’s profile within a family.The results show that there are division of activities in the families of women-online taxibikers. The production activities in those families are carried out together, both husband and wife work together to earn a living. It proves that there are equal opportunities for the husband and wife in carrying out production activities. Whereas in reproductive activities, even though there is already a husband's involvement, the wife has more dominant role. In social activities, there are activities-differentiation for husband and wife although they are both involved in community activities. Men's activities are still regarded to be public-oriented, while women's activities are still related to reproductive matters. Regarding the access-control division, it is now done by the woman or wife more oftenly. The factors that influence the distribution of activities and access control in the families of women-online taxibikers “Go-Jek” are economic, cultural, and educational factors. It can be concluded that gender relations in the families of women-online taxibikers “Go-Jek” in Surakarta have complementary relationships. Although there are some differences in roles, they have the same goal, namely family harmony.